Qualitative Evaluation of a Complex Intervention to Improve Rheumatic Heart Disease Secondary Prophylaxis. Issue 14 (17th July 2018) - Read, Clancy; Mitchell, Alison G.; de Dassel, Jessica L.; Scrine, Clair; Hendrickx, David; Bailie, Ross S.; Johnston, Vanessa; Maguire, Graeme P.; Schultz, Rosalie; Carapetis, Jonathan R.; Ralph, Anna P.
Abstract : Background: Rheumatic heart disease is a high‐burden condition in Australian Aboriginal communities. We evaluated a stepped‐wedge, community, randomized trial at 10 Aboriginal communities from 2013 to 2015. A multifaceted intervention was implemented using quality improvement and chronic care model approaches to improve delivery of penicillin prophylaxis for rheumatic heart disease. The trial did not improve penicillin adherence. This mixed‐methods evaluation, designed a priori, aimed to determine the association between methodological approaches and outcomes. Methods and Results: An evaluation framework was developed to measure the success of project implementation and of the underlying program theory. The program theory posited that penicillin delivery would be improved through activities implemented at clinics that addressed elements of the chronic care model. Qualitative data were derived from interviews with health‐center staff, informants, and clients; participant observation; and project officer reports. Quantitative data comprised numbers and types of "action items, " which were developed by participating clinic staff with project officers to improve delivery of penicillin injections. Interview data from 121 health‐center staff, 22 informants, and 72 clients revealed barriers to achieving the trial's aims, including project‐level factors (short trial duration), implementation factors (types of activities implemented), and contextual factors (high staff turnover and the complex sociocultural environment). Insufficient actions were implemented addressing "self‐management support" and "community linkage" streams of the chronic care model. Increased momentum was evident in later stages of the study. Conclusions: The program theory underpinning the study was sound. The limited impact made by the study on adherence was attributable to complex implementation challenges.